Impact of Corporate Social Responsibility on the Performance of Pharmaceutical Companies in Nepal - Dwibedi, Lalan (Academic Voices: A Multidisciplinary Journal, 2019)
The purpose of this study is to investigate the impact of corporate social responsibility (economic, philanthropic and environmental responsibility) on Nepalese Pharmaceutical Company’s performance and its relationship with CSR variables. The study revealed that positive relationships between CSR variables and all the three variables are strongly related to company performance. The economic responsibility has the highest impact on company’s performance followed by the environmental responsibility and then the philanthropic responsibility. This study highlighted that being socially and environmentally responsible is not only good for society but also excellent for increasing and preserving shareholder value and corporate image. As for practitioners, there is clearly a need to improve their CSR activities and practices that particularly address the enhancement of consumer protection, product quality or provide incentives and overall organizational performance. CSR policy should be formulated clearly within Pharmaceutical industries but still the CSR is implemented insignificance by Nepalese pharmaceuticals companies.